Repeated Sprint Ability in Youth Soccer Players: Independent and Combined Effects of Relative Age and Biological Maturity - Duarte, João P. (2019)
The objective of the study was to examine the effects of the relative age effect (RAE) and predicted maturity status on body size and repeated sprint ability (RSA: 7 x 34.2 m / 25 s interval) in youth soccer. The sample was composed of 197 male players aged 13-14 years. Body mass, stature, and sitting height were measured, RSA was assessed in the field, and age at peak height velocity (APHV) was predicted. Factorial ANOVA tested the independent and combined effects of RAE given by birth quarters (BQs) and maturity status on dependent variables. Players born in the second birth quarter (BQ2) were significantly taller (F = 4.28, p < 0.01) than their peers born in BQ1 and BQ3. Additionally, players born in BQ2 performed better than players born in BQ4 in RSA total time and ideal time (F ranged between 4.81 and 4.90, p < 0.01), while players born in BQ1 exhibited a lower RSA fatigue index compared to those born in BQ4 (F = 2.90, p < 0.05). The interaction of the BQ and maturity status was a significant source of inter-individual variation for body size (F ranged between 64.92 and 105.57; p < 0.01) and RSA output (F ranged between 4.082 and 6.76; p < 0.05). In summary, being relatively older and, simultaneously, advanced in maturity status corresponds to a substantial advantage in characteristics that are related to soccer-specific fitness.